„HOMO TRANSFORMENS” по Пелевину („современные” оборотни, вампиры и андроиды – постмодернистские вариации Виктора Пелевина) - Pańkowska, Ewa (Studia Rossica Posnaniensia, 2019)
Victor Olegovich Pelevin undoubtedly belongs to the most popular contemporary Russian writers. He is recognized as one of the leading representatives of Russian postmodernism. The purpose of this article is to show distinguishing features and characteristics of Pelevin’s “non-human beings”: at first to discuss Pelevin’s “postmodernist and eclectic” conception of “supernatural creatures”: werewolves and vampires (Pelevin deconstructs “werewolf and vampire discourses”), and secondly, to show Pelevin’s point of view on human–robot relationships. The following Pelevin’s novels are the subject of the analysis in this paper: The Sacred Book of the Werewolf (2004), Empire “V”. The Story of a Real Superman (2006), S.N.U.F.F. (2011), Batman Apollo (2013).